The Ethical Issues of Political Conspiracy Theories - Babajanyan, Levon (Bulletin of Yerevan University E: Philosophy, Psychology, 2022)
Conspiracy theories have a reasonably bad connotation. It is believed, that the epistemological deficiency of conspiracy theories spoils the adequate perception of social-political reality. However, in democratic societies, the epistemological deficiency of any theory couldn’t be considered a sufficient ethical argument for rebutting the spread of such theories, as in that case it would be obligatory to prevent the spread of the other epistemologically deficient theories (such as religious theories etc.). At the same time, it is mostly accepted, that the spread of political conspiracy theories threatens democratic societies, as they decrease the overall level of trust between the members of the society, the trust in government and state institutions. Thus, a reasonable argument is needed for the prevention the spread of political conspiracy theories. The article suggests, that mainly the ethical unacceptability of political conspiracy theories and their threats to the democratic tenets of the organization of society could be a reasonable argument for rebutting conspiracy theories. Thus, mostly the ethical deficiency of political conspiracy theories gives a “moral right” to the state and the society for the elaboration and actualization of the prevention policy of their spread.
Keywords: Conspiracy Theories; Political Conspiracy Theories; Total Conspiracy Theories; Democracy; Epistemological deficiency; Ethical deficiency